(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research was conducted with the following objectives: (1). To find out, analyze and discover the essence of law enforcement in eradicating criminal acts of corruption in the procurement of government goods and services in Central Sulawesi Province. (2). To find out, analyze and discover the implementation of law enforcement on corruption in the procurement of goods and services in Central Sulawesi Province. (3). To find out, analyze and find the factors that influence law enforcement in eradicating corruption in the procurement of goods and services in Central Sulawesi Province. This study uses primary data through a survey of 55 samples of law enforcement officers, five police officers, five prosecutors, five judges, five lawyers and 35 state civil servants from various agencies. The survey was conducted from April to June 2023. The results of this study indicate that the essence of law enforcement of criminal acts of corruption in the procurement of government goods and services is the creation of law enforcement of criminal acts of corruption in the procurement of government goods and services, which is an attempt to realize the ideas of justice, legal certainty and social benefits come true. (2). Implementing efforts to eradicate corruption in procuring government goods and services in Central Sulawesi Province has not been optimal. (3). The factors influencing law enforcement in eradicating corruption in the procurement of government goods and services in Central Sulawesi Province are the factors of legal substance, legal structure, legal awareness, and legal culture. This means that if law enforcement for eradicating criminal acts of corruption in the procurement of goods and services is optimized, this can save state financial losses, and these funds can be used for national development.